2014
DOI: 10.1186/s12905-014-0138-1
|View full text |Cite
|
Sign up to set email alerts
|

Men’s knowledge and attitudes about cervical cancer screening in Kenya

Abstract: BackgroundA number of studies have identified male involvement as an important factor affecting reproductive health outcomes, particularly in the areas of family planning, antenatal care, and HIV care. As access to cervical cancer screening programs improves in resource-poor settings, particularly through the integration of HIV and cervical cancer services, it is important to understand the role of male partner support in women’s utilization of screening and treatment.MethodsWe administered an oral survey to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
50
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 16 publications
16
50
1
Order By: Relevance
“…Therefore it is important for men to know that as they are being involved in sexual relations with more than one woman, the risk of HPV transmission in their spouses" increases. Similar results on low level of knowledge on the cervical cancer cause have also been reported by several studies [18][19][20]16] also found that only 20 % of the study participants knew HPV as a cause of cervical cancer. This is unlike a Ugandan study where some participants believed that too much sex would cause injury to the cervix which might later develop into cervical cancer [20].…”
Section: Knowledge On Cervical Cancer Causesupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore it is important for men to know that as they are being involved in sexual relations with more than one woman, the risk of HPV transmission in their spouses" increases. Similar results on low level of knowledge on the cervical cancer cause have also been reported by several studies [18][19][20]16] also found that only 20 % of the study participants knew HPV as a cause of cervical cancer. This is unlike a Ugandan study where some participants believed that too much sex would cause injury to the cervix which might later develop into cervical cancer [20].…”
Section: Knowledge On Cervical Cancer Causesupporting
confidence: 89%
“…Participants who had gone beyond primary school level were more knowledgeable compared to their counterparts with primary school education and below. This implies that high illiteracy level can impact positively on knowledge about cervical cancer as supported by Aswathy [21,16] who both observed that men who had education beyond secondary school were more knowledgeable whilst those who had gone up to primary or less had the least knowledge scores.…”
Section: Knowledge On Signs and Symptomsmentioning
confidence: 88%
See 2 more Smart Citations
“…5 Jolle et al also observed significantly greater knowledge about cervical cancer among men with higher levels of education in their study among men in Kenya. 16 Comparatively low awareness was observed among husbands with technical and unskilled job.…”
Section: Discussionmentioning
confidence: 99%